'Here today, gone tomorrow': the risks and rewards of port chaplaincy. Issue 2 (3rd April 2023) - Gilliat-Ray, Sophie; Smith, Graeme; Cadge, Wendy; Sampson, Helen; Turgo, Nelson
ABSTRACT: This paper documents the findings of an ESRC-funded project about religion in the context of the international global shipping industry, with particular focus on the work of port chaplains. We describe the physical, emotional, spiritual and financial risks involved in port chaplaincy work, and the way this form of religious employment is distinctly gendered. But the risks and challenges of port chaplaincy are considered alongside its intrinsic rewards and potential for professional fulfilment, most especially through the traffic of material goods and the sharing of hospitality that enable relationships between chaplains and seafarers. Our work contributes to the scholarly field of workplace chaplaincy by providing an empirical case study of port chaplains who typically operate as 'lone workers' as they minister to seafarers whose labours are so vital to the global economy. We consider the fact that lone workers can be vulnerable to exclusion from effective management practices which otherwise assume face-to-face interaction.